Dietary lacto-sacc improved growth performance, food acceptability, body indices, and basic hematological parameters in empurau (Tor tambroides) fries reared in the aquaponics system - Mohammad Bodrul, Munir; Sharifah Lia Farliana, Wan Alias; Roslianah, Asdari; Md. Abdul, Hannan; Md. Jahidul, Hasan (Taylor & Francis Group, 2022)
Slow growth rate of empurau (Tor tambroides) fish is reported impeding its’ aquaculture practice extensively in Malaysia. It mainly occurs at the fry to fingerling phase. Hence, the present research evaluated the dietary lacto-sacc feed supplement on the growth performance and health status of T. tambroides fries. The fish growth was outperformed significantly (P<0.05) after 12 weeks in fish fed with the lacto-sacc supplemented fish feed compared to the non supplemented control diet. Alike the growth performance, the basic hematological parameters were significantly (P<0.05) improved. This study was the first attempt to indicate the suitability of dietary lacto-sacc for empurau fries nursery in the aquaponics system. Although this study was performed in four types of aquaponics systems, the factorial analysis confirmed that diet had a strong effect for this occurrence.